INVESTIGATION OF CONTACT PARAMETERS IN CYLINDRICAL METAL-POLYMER SLIDING GUIDES - Чернець, Мирон Васильович; Корнієнко, Анатолій Олександрович; Федорчук, Світлана Володимирівна; Іщенко, Анатолій Олексійович; Радіоненко, Олександр Васильович (Problems of Friction and Wear, 2021)
Guides (linear plain bearings) of reciprocating motion are widely used in many areas of human activity. However, at present there are no reasonable methods for their calculation, in particular metal-polymer guides. The method of calculation of contact parameters in cylindrical metal-polymer sliding guides is given. On the example of antifriction polymer composite material DK6 on epoxy basis, used for restoration of tribotechnical sliding systems, the influence of load, diameter of the bashing and radial clearance on the maximum contact pressures and their distribution in the guide is investigated. Quantitative and qualitative regularities of dependence of contact pressures on the accepted factors of influence are established: at loading increasing four times the maximum contact pressures and contact angles will increase twice irrespective of change of sizes of a radial clearance and diameter of a basis; increasing its diameter leads to a directly proportional decrease in maximum contact pressures; doubling the radial clearance leads to an increase in pressure, regardless of changes in the magnitude of the load and the diameter of the base. Regularities of change of contact parameters from the specified factors are given graphically.